You should evaluate the limit of the function `e^x` under the given condition, such that:

`lim_(x->-oo) e^x = e^(-oo)`

Using negative power property yields:

`a^(-b) = 1/a^b`

Reasoning by analogy yields:

`e^(-oo) = 1/e^oo = 1/oo = 0`

**Hence, evaluating the limit of the given function `e^x` , under the given conditionsm, yields `lim_(x->-oo) e^x = 0.` **

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now